The impacts of C1q/TNF-related protein-15 and adiponectin on Interleukin-6 and tumor necrosis factor-α in primary macrophages of patients with coronary artery diseases. (June 2021) - Ahmadi, Reza; Fadaei, Reza; Shokoohi Nahrkhalaji, Abolfazl; Panahi, Ghodratollah; Fallah, Soudabeh
Abstract: Atherosclerosis is a progressive inflammatory disease characterized by the accumulation of lipids in the arterial wall. Inflammation plays a key role in the pathogenesis of atherosclerosis and some previous studies have shown the role of adipokines during the inflammatory process of atherosclerosis. Therefore, the present study aimed to evaluate the impacts of adiponectin and CTRP15 on inflammatory cytokines secretions from THP1 and primary macrophages. Methods: THP1 monocytes were differentiated to macrophages and primary monocytes were then isolated from patients with coronary artery disease and controls who were differentiated to macrophages. Macrophages were treated with LPS, LPS+adiponectin, and LPS+CTRP15. Results: Adiponectin and CTRP15 have reduced IL-6 and TNF-α secretions from LPS-induced THP1 macrophages, and the CTRP15 indicated a more potent anti-inflammatory property compared to adiponectin. In addition, adiponectin reduced cytokines' expressions and secretions in primary macrophages of both patient and control groups. However, CTRP15 has only reduced cytokines' expressions and secretions in controls and it was not able to ameliorate inflammation in macrophages of CAD patients. Conclusion: The results of the present study indicate anti-inflammatory impact of adiponectin and CTRP15, while this property was stronger for CTRP15. In addition, it seems likely that anti-inflammatory CTRP15′s impact on macrophages in the CAD patients was weaker than macrophages from the controls.